Thermally evaporated perovskite ultrathin films for quantum well applications - Rachel Emmanuelle Raphael (Nanyang Technological University, 2023)
Our world is struggling with the consistently growing demand for energy, exacerbated by the challenges and depleting supply of fossil fuels, which have long served as the primary energy source. As a response to these challenges, mainly the environmental concerns associated with these sources, nations worldwide are transitioning away from fossil fuels and shifting towards cleaner and more sustainable energy solutions. In this global shift, solar photovoltaic (PV) technology stands out as a promising alternative, considering the abundant solar irradiance available on earth. Over the past decade, researchers have explored perovskite materials due to their advantageous attributes, notably their cost-effectiveness and relatively simple processing. In addition to investigating novel materials, efforts have been made to explore innovative structures to further optimize device performance. This project delved into the exploration of integrating perovskite materials within an innovative PV structure, specifically, the quantum well structure. By combining the promising attributes of thermally evaporated perovskite materials with the optimistic potential of quantum well structure, this project extended its implication beyond mere performance enhancement. This report thoroughly assesses the remarkable improvements in absorption capacity resulting from having two different materials in the implementation of a quantum well structure. It also discusses the quantum confinement effect, as an outcome of depositing ultra-thin films to achieve such structure. While highlighting the promising benefits, limitations and trade-offs associated with the structure are also carefully considered in this report. By the end of the project, it was proven that substantial enhancement in light absorption could be achieved. The spectrum of light absorption range was successfully extended into the infrared region, starting from a wavelength of 1000 nm, a notable increase from only around 780 nm achievable with a single-material perovskite. This newfound capacity for light absorption holds promise for further advancements in PV device performance, given that absorption is a crucial factor in a solar cell device.